A NUMERICAL MODEL OF DEFORMATION AND FLUID-FLOW IN AN EVOLVING THRUST WEDGE - Strayer L.M.; Hudleston P.J.; Lorig L.J. (My University, 2001)
To investigate deformation and fluid-flow in an actively deforming tectonic wedge, we model the evolution of a large, two-dimensional (100km long, 5km thick), mechanically and hydrologically homogeneous and isotropic pile of sedimentary strata that is deformed to become a thrust wedge. We compare both 'dry' and 'wet' cases, in order to illustrate: (1) the relative importance of fluids on wedge evolution, and (2) the effect of brittle deformation on fluid-flow. We use an elastic-plastic constitutive relation, including a Mohr-Coulomb failure criterion and a non-associated flow rule, and coupled fluid flow, with bulk rock properties that approximate typical foreland sedimentary strata. Simulations are made both with and without dilation. The model is fully dynamic, but inertial forces remain small.Results show that deformation within the wedge is accommodated by reverse-slip movement on shear bands, which migrate in both directions through the wedge as both fore- and back-thrusts. The model has features predicted by the critical-taper theory: (1) overall wedge geometry; (2) crudely self-similar growth during evolution; (3) more intense deformation toward the rear of the wedge. The models show strong overall in-sequence faulting behavior with major thrusts isolating relatively undeformed packages, which are moved in a piggyback manner upon the active thrusts. Intermittent out-of-sequence faulting does however occur, in order to maintain the wedge taper.Fluid-flow in the deforming wedge is dominated by topography, but is also strongly affected by dilational plastic deformation. In all simulations, there is focused fluid flow within fault zones. When mechanical time-stepping is shut off (uncoupled), flow systems evolve to steady-state where inflow equals outflow. By subtracting the two 'states' we isolate the mechanical fluid response from the total coupled system response. The mechanical fluid response is manifest as contours of head and pressure difference and focusing of fluid-flow in areas of active deformation. In non-dilational simulations, these zones are quite localized and are a result of the contrasting stresses in and adjacent to a brittle shear zone. In simulations with dilation, the zones of head and pressure difference are broad and regional in extent. They are ten times greater in magnitude than in non-dilation simulations, and they track a rock-damage front that moves through the wedge.
Keywords: TOPOGRAPHY; FLUID-FLOW; WEDGE